What the Bible Says About Education: A Critical Review of Biblical Education and Its Relevance in the Era of Globalization - Katuuk, Antoinette L Grace; Mailangkay, Sonny D J; Weol, Wolter; Siang, Jhoni Lagun (International Journal of Education, Information Technology, and Others, 2024)
Understanding the meaning of education is very important for the formation of human character and intellect. In the Christian context, the Bible is the main reference source in understanding education in accordance with God's will. The meaning of education in this context is teaching, rules, regulations and all things related to educating, instructing and disciplining God's people, namely His human creation. However, in the current era of globalization, the challenges and dynamics of education have experienced significant changes. This article aims to conduct a critical review of the concept of the meaning of education according to the Bible and criticize its relevance in the digital era of globalization. Through studying Bible verses related to education, several basic things were identified, such as the importance of knowing God through reading the Bible, examining the purpose of education and God's teachings from the Old Testament to the New Testament and the time of the Holy Spirit. However, advances in digital technology have changed the landscape of the meaning of education, giving rise to new challenges, namely distractions from the meaning of education in the Bible. This article explores how the teaching or educational values ​​that God gave to Adam and Eve reached the Israelites as HIS chosen nation, during the Old Testament, the New Testament and so on up to the present. Whether teaching or upbringing through God speaking directly, through the voices of prophets, apostles and the Holy Spirit: can it still be applied adaptively and transformatively to answer educational challenges in the era of globalization? This review emphasizes the need for a balanced educational approach between Biblical values ​​and technological advances, starting with motivating a person so that there is a desire to find out through the desire to read the Bible. This will enable people, especially the younger generation of Christians, to understand the holistic meaning of education according to the Bible, which strengthens faith, character and skills needed to face the complexities of the times.